Optimizing the Respiratory Pump: Harnessing Inspiratory Resistance to Treat Systemic Hypotension - Víctor A. Convertino; Kathy L. Ryan; Caroline A. Rickards; Steven Glorsky; Ahamed H. Idris; Demetris Yannopoulos; Anja Metzger; Keith G. Lurie (2011)
We review the physiology and affects of inspiration through a low level of added resistance for the treatment of hypotension. Recent animal and clinical studies demonstrated that one of the body9s natural response mechanisms to hypotension is to harness the respiratory pump to increase circulation. That finding is consistent with observations, in the 1960s, about the effect of lowering intrathoracic pressure on key physiological and hemodynamic variables. We describe studies that focused on the fundamental relationship between the generation of negative intrathoracic pressure during inspiration through a low level of resistance created by an impedance threshold device and the physiologic sequelae of a respiratory pump. A decrease in intrathoracic pressure during inspiration through a fixed resistance resulting in a pressure difference of 7 cm H2O has multiple physiological benefits, including: enhanced venous return and cardiac stroke volume, lower intracranial pressure, resetting of the cardiac baroreflex, elevated cerebral blood flow oscillations, increased tissue blood flow/pressure gradient, and maintenance of the integrity of the baroreflex-mediated coherence between arterial pressure and sympathetic nerve activity. While breathing has traditionally been thought primarily to provide gas exchange, studies of the mechanisms involved in animals and humans provide the physiological underpinnings for "the other side of breathing": to increase circulation to the heart and brain, especially in the setting of physiological stress. The existing results support the use of the intrathoracic pump to treat clinical conditions associated with hypotension, including orthostatic hypotension, hypotension during and after hemodialysis, hemorrhagic shock, heat stroke, septic shock, and cardiac arrest. Harnessing these fundamental mechanisms that control cardiopulmonary physiology provides new opportunities for respiratory therapists and others who have traditionally focused on ventilation to also help treat serious and often life-threatening circulatory disorders.